The Influence of Product Quality and Service Quality on Customer Satisfaction at Mujigae Resto Mall Summarecon Bekasi - Pradana, Agustian Adi; Yanti, Vera Agustina; Rafik, Ahmad (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Businesses in the food industry experienced significant growth during the crisis due to the high demand for food and beverages as a basic need. This has encouraged the rapid development of various types of culinary businesses, from traditional cuisine to fast food, with increasingly diverse menu offerings. In Indonesia, especially the younger generation, the increasing interest in Korean cuisine such as toppoki, bibimbap, and jajangmyeon is triggered by the popularity of K-pop and Korean dramas. This phenomenon is reflected in the increasing number of Korean restaurants present in Indonesia, with its own strategies and advantages in attracting consumer interest. This study analyzes the influence of product quality and service quality as independent variables on customer satisfaction as a dependent variable at Mujigae Resto, Summarecon Mall Bekasi, both partially and simultaneously. The research method used is a quantitative approach with Non Probability Sampling technique and Accidental Sampling method. Data was obtained through a questionnaire from 50 Mujigae Resto customers at Summarecon Mall Bekasi. The results of the study show that product quality and service quality, both partially and simultaneously, have a significant influence on customer satisfaction. Overall, product quality and service quality contributed 71% to customer satisfaction, while the remaining 29% was influenced by other factors that were not studied. The R Square value for product quality is 60.7% and for service quality is 68%, indicating that service quality has a dominant influence on customer satisfaction at Mujigae Resto, Mall Summarecon Bekasi.